(untitled) (Tempo e Argumento, 2021)
This article performs a critical bibliographic review on discrimination and segregation practices in occupied Palestine. The considerations of different authors are exposed, divided as they understand the occupation, but above all from the historical forces that constitute the State of Israel as an ethnocracy, namely: nationalism, colonialism and capitalism. Therefore, ethnocracy is the concept that converges the different interpretations presented here, emphasizing their approximation. Furthermore, the bibliography is compared to UN and NGO human rights reports, demonstrating its complementarity